A Scientometric Analysis on Shariah Accounting Standard - Uula, Mimma Maripatul; Azzam, Hilmy Abdullah (SMART Insight, 2024)
This research explores sharia accounting standards by mapping recent trends in the literature through bibliometric analysis using Biblioshiny in R Studio. This research identifies three main clusters based on network analysis: the green cluster, which focuses on the challenge s of sharia accounting standards; the red cluster, which emphasizes Sharia Financial Reporting Compliance; the orange cluster, which highlights the topic of Sharia Accounting Standards and Waqf; the purple cluster explains Board effectiveness in Shariah reporting; and the blue cluster examines internal audit in sharia finance. Malaysia, Indonesia and the United Kingdom stand out in this area, reflecting their significant contributions to advancing research. Key topics in the theme quadrants include Islamic, financial, accounting, governance, sharia, standards, and banks. The intersection between Islamic accounting standards and banks emerged as a promising area for further exploration due to the potential growth of Islamic finance globally. This research underscores the need to optimize Islamic accounting standardization through digitalization and technological innovation as well as enhancing transparency and accountability. In addition, harmonization of international standards and strong Shariah compliance mechanisms are essential for the successful implementation of Islamic accounting standardization in the global realm. Overall, this chapter provides valuable insights into the evolving landscape of Islamic accounting standards and highlights important areas for future research.